KPPU, Prohibition of Monopoly and Unfair Business Competition: Policy and Organizational Perspective - Hersusetiyati Hersusetiyati; Tatang Sudrajat (Universitas Diponegoro, 2023)
National improvement withinside the monetary field, will boost up the fulfillment of people's welfare. A wholesome monetary lifestyle calls for identical possibilities for residents to do commercial enterprise. The coverage of prohibiting monopoly and unfair commercial enterprise opposition is a strategic remember for the countrywide economy. The established order of the Business Competition Supervisory Commission (KPPU) with state/authority’s policies is an essential step in the direction of monetary democratization. Using normative juridical strategies and literature, it seems that the choice of the state/authorities through issuing Law Number five of 1999, Government Regulation Number forty four of 2021, and Presidential Decree Number seventy five of 1999 is a public coverage concerning the essential function of KPPU and the prohibition of monopolistic practices and unfair commercial enterprise opposition. This is an important basis for the KPPU's determination of operational policies. There are arrangements for KPPU's organizational dimensions in the three regulations, namely objectives, formalization, standardization, hierarchy of authority, specialization, professionalism, and organizational size, some of which are not regulated adequately. This will determine the effectiveness of the implementation of its duties and authorities as a supervisory agency. KPPU is also faced with challenges and political contexts that are not easily aligned with the independent nature of its organization. In the context of democracy, KPPU needs to strengthen its position by continuously improving the quality of its performance. It is necessary to improve several dimensions of the KPPU's organization in the regulations that govern it.